Targeting the CD47/Calreticulin axis in Triple Negative Breast Cancer using HA grafted Chitosan nanoparticles loaded with Doxorubicin and Polygodial - Emara, Hadir M (AUC Knowledge Fountain, 2026)
Background: Triple-negative breast cancer (TNBC) is considered the most aggressive subtype of breast cancer. Although progress in cancer treatment has led to better results for different types of breast cancer, TNBC remains particularly challenging due to persistent resistance to both chemotherapy and immunotherapy. This resistance ultimately renders chemotherapy less effective and is frequently associated with substantial side effects. Immunosurveillance significantly impacts the onset of cancer, the rise of resistance to therapies, and the likelihood of tumor recurrence. In this immunomodulatory process, Cluster of Differentiation 47 (CD47) and Calreticulin (CALR) are two key regulators. CD47 expression is strongly linked to anti-phagocytic signaling, whereas the role of CALR expression in immunomodulation and TNBC progression remains contradictory. Many natural compounds, including Doxorubicin (DOX), have demonstrated strong anti-cancer activity against TNBC. However, like other chemotherapeutic agents, their use is often limited by low efficacy, significant side effects, and a high tendency for the development of resistance. Aim: The primary objectives of this study were, first, to explore the effect of sublethal chemotherapy doses on surrogate markers of immune cells that might be involved in chemotherapeutic resistance. Building on this, the study aimed to leverage this potential chemoresistance mechanism to develop a safer and more effective therapeutic platform for treating TNBC. To achieve these goals, two main strategies were proposed: the use of natural chemotherapeutic agents in combination at sublethal doses, and the implementation of nanoparticles (NPs) for receptor-mediated drug delivery. Methods: This comprehensive study was divided mainly into two main parts. First, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assays of DOX and Polygodial (PG) were conducted on MDA-MB-231 cells to determine their respective sublethal concentrations. Subsequently, total RNA was extracted, and quantitative real-time polymerase chain reaction (qPCR) was performed to evaluate the impact of these sublethal doses, both as monotherapy and in combination therapy, on the expression levels of CALR and CD47 in MDA-MB-231 cells. Secondly, HA-grafted CTN NPs (HA-CTN NPs) were synthesized, co-loaded with DOX and PG, and extensively characterized. MDA-MB-231 cells were then treated in vitro with the nano formulation. Sublethal concentrations were identified using the MTT assay, followed by quantitative analysis of CD47 and CALR mRNA expression levels in NP treated cells compared to untreated controls. Results: Treatment of MDA-MB-231 cells with either DOX or PG at sublethal doses resulted in a significant upregulation of CD47 mRNA expression. Notably, CALR mRNA expression was also elevated, particularly at the lowest sublethal concentration of DOX, compared to vehicle-treated control cells. A reversal of immunomodulatory resistance was achieved by sublethal doses of a combination of DOX and PG, which was further amplified through drug delivery via HA-CTN nanoparticles. Combination and nano-formulated treatments led to a marked reduction in intracellular CD47 and CALR expression levels, along with a significant shift in the CD47/CALR mRNA ratio to below 1. Conclusion: Sublethal doses of the DOX and PG combination were able to evade CD47/CALR-surrogate marker of immunosurveillance in TNBC cells in vitro, outperforming DOX or PG monotherapy and untreated controls. Since immunomodulation is a key factor in cancer development, spread, and recurrence, our findings propose a promising strategy for both effective and safe chemotherapy, as well as a potential option for maintenance therapy. Notably, the HA-CTN nano formulation alone exhibited immunomodulatory properties, and when loaded with the combination therapy, it achieved comparable levels of CD47/CALR mRNA expression at significantly lower drug doses.